The Effectiveness of Clinical Practicum in Psychiatric Hospitals in Enhancing Mental Health Literacy and Reducing Mental Illness Stigma among Students - Nana Wildana; Melania Hidayat; Marthoenis Marthoenis (GLOBAL HEALTH SCIENCE GROUP, 2026)
Clinical practice in psychiatric hospitals is a crucial learning method for preparing competent healthcare professionals; however, low mental health literacy and persistent stigma among students often trigger anxiety and stress during training. This study aimed to evaluate the effectiveness of clinical practicum in improving mental health literacy and reducing stigma, as well as to analyze determinants of changes in students’ mental health status based on practice duration, age, and gender. This study employed a quantitative analytical design with a quasi-experimental one-group pretest–posttest approach involving 569 health profession students using total sampling. Data were collected through validated instruments, including the Mental Health Literacy Scale (MHLS) (0.876), the Opening Minds Scale for Health Care Providers (OMS-HC) (0.870), and the Depression Anxiety Stress Scale (DASS-21) (0.918), and analyzed using multiple linear regression. The results showed that clinical practicum significantly improved mental health literacy (p = 0.0007) and reduced anxiety (p = 0.0204) and stress (p = 0.0287), while stigma did not change significantly (p = 0.3913). Multivariate analysis revealed that a one-month practice duration was the most effective period, with greater reductions in anxiety (B = −3.714; p = 0.000) and stress (B = −3.549; p = 0.000) compared to a two-week duration. Increased literacy significantly contributed to reductions in anxiety (p = 0.010) and depression (p = 0.045), whereas stigma reduction was not significant, and older students showed slower decreases in anxiety (p = 0.029). Overall, clinical practicum improves cognitive aspects (literacy) but has limited impact on perceptual aspects (stigma).